Research progress on sirtuin family genes in colorectal cancer - Liu, Tong; Wu, Tianhua; Luo, Lijun; Li, Wei; Zhang, Minglin (Frontiers in Oncology, 2025)
Sirtuins are a highly conserved family of NAD+-dependent deacetylases involved in regulating critical biological processes such as cell survival, antioxidation, gene transcription, proliferation, differentiation, DNA repair, and mitochondrial function. Recent studies have revealed that altered expression of sirtuin family genes in mammals is closely linked to the development of various diseases, including metabolic disorders, ageing, and cancer. In colorectal cancer (CRC), sirtuins play dual regulatory roles, modulating tumour cell proliferation, migration, invasion, and apoptosis while also activating pro-oncogenic signalling pathways or suppressing tumour progression, depending on context. This review systematically summarizes the research progress on sirtuin family genes in CRC, highlighting their dual roles (pro-tumorigenic and tumour-suppressive) and molecular mechanisms. These findings underscore the potential of sirtuins as therapeutic targets in CRC. The development of selective activators or inhibitors, combined with metabolic interventions or immunotherapy, may provide novel strategies for precision CRC treatment.